Les effets d’un programme bilingue d’apprentissage de l’écrit (initiative ELAN-Afrique) à l’école primaire en Afrique subsaharienne francophone - Isabelle Nocus; Philippe Guimard; Agnès Florin (Recherches en Éducation)
This study assessed the impact of the program’s teaching methods ELAN-Africa for reading and writing in national languages (L1) and French (L2), at the first two years of elementary school (Grade 1 year 1 and Grade 1 year 2) in eight Sub-Saharan African countries. The cross-lingual effects between L1 and L2 was also investigated. 2 700 pupils were assessed at 3 times of measure during the 2 years (at the beginning of Grade 1 year 1, at the end of Grade 1 year 1 and at the end of Grade 1 year 2). Approximately the half of the pupils was enrolled in experimental classrooms implied in the program (10 by country) and the other in control classrooms. At the beginning of Grade 1 year 1, the protocol of assessment included 5 tests: print concepts and letters knowledge, vocabulary, phonological awareness and oral comprehension. At the end of Grade 1 year 1, two reading tests were added: reading words and a one-minute reading. At the end of Grade 1 year 2, several tests of the last assessment were preserved and 2 others were added: written comprehension and spelling. The positive effect of the program was found in 7 of the 8 countries, but with a varying efficacy according to writing skills, the contexts and the countries. Recommendations were proposed to improve the program and to think its extension into other countries.